The Relationship of General Health Condition with Safety Attitudes and Demographical Specifications in Workers of Car after-Sale Services Workshops Iran 2019 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Health condition of workers affects their productivity. The relationship between generalhealth and safety attitudes is not quite clear.Objective: The present paper is an attempt to examine the relationship of general health condition withsafety attitude and demographical specifications of workers at car after-sale services workshops in ArdabilIran.Materials and Method: The study was carried out as a descriptive-analytical cross-sectional study. Thesample group consisted of 650 workers in small car after-sale services workshops located in Ardabil City.Three questionnaires including a demographical form, the General Health questionnaire (GHQ-28), and thesafety attitude inventory were used for data gathering. The collected data was analyzed in SPSS19.Results: The mean score of safety attitude was 71.05±2.3 and the mean score of general health was24.96±3.35. The score of general health had a significant relationship with age group, work experience,marital status, education level, and history of work incident. The mean scores of safety attitude wassignificantly different depending on age group, work experience, workshop ownership status, marital status,education level, income, and history of work accident.Conclusion: The subjects had a low safety attitudes score and high probability of general heath disorders.General health condition was directly related to safety attitude of the participants. Therefore, providingapplied educations based on the workers’ needs to increase awareness and improve safety attitudes ofworkers can lead to a decrease in the rate of work accidents and a higher general health in the workers.